Biomarkers of exposure to tobacco smoke and environmental pollutants in mothers and their transplacental transfer to the foetus. Part I: bulky DNA adducts - Topinka, J; Milcova, A; Libalova, H; Novakova, Z; Rossner, P; Balascak, I; Sram, R J (Mutation research, 2009)
(32)P-postlabelling and PAH-ELISA using the antiserum #29 were employed to analyze DNA adducts in venous and umbilical cord blood and the placenta of 79 mothers giving birth to 80 living babies in Prague (Czech Republic). Ambient air exposure was measured by stationary measurements of basic air pollutants (PM2.5, c-PAHs) during the entire pregnancy. Tobacco smoke exposure was assessed by questionnaire data and by plasma cotinine levels. The total DNA adduct levels in the lymphocytes of mothers and newborns were elevated by 30-40% (p<0.001) compared with the placenta. B[a]P-like DNA adduct (adduct with the identical chromatographic mobility on TLC as major BPDE derived DNA adduct) levels were elevated in the blood of mothers compared with the placenta and the blood of newborns (p<0.05 and p<0.01). In tobacco smoke-exposed mothers, higher DNA adduct levels in the blood of mothers and newborns compared with the placenta were found (p<0.001), whereas the total and B[a]P-like adduct levels were comparable in the blood of mothers and newborns. B[a]P-like adducts were elevated in the blood of mothers unexposed to tobacco smoke compared with that of corresponding newborns and the placenta (p<0.01). Total and B[a]P-like DNA adducts were increased in the placenta of tobacco smoke-exposed compared with unexposed mothers (p<0.001 and p<0.01). In lymphocytes of tobacco smoke-exposed mothers, the comparison of total adduct levels (1.18+/-0.67 vs. 0.92+/-0.28) and B[a]P-like DNA adducts (0.22+/-0.12 adducts/10(8) nucleotides vs. 0.15+/-0.06 adducts/10(8) nucleotides) with newborns indicated a 30-40% increase of adducts in mothers. Almost equal PAH-DNA adduct levels were detected by anti-BPDE-DNA ELISA in the placenta of tobacco smoke-exposed and -unexposed mothers. Our results suggest a protective effect of the placental barrier against the genotoxic effect of some tobacco smoke components between the circulation of mother and child. We found a correlation between adduct levels in the blood of mothers and newborns.
Keywords: polycyklické aromatické uhlovodíky; maternofetální výměna látek; novorozenec; Infant, Newborn; Maternal Exposure; Humans; Pregnancy; kotinin; Lymphocytes; lymfocyty; Placenta; 7,8-Dihydro-7,8-dihydroxybenzo(a)pyrene 9,10-oxide; Female; mladý dospělý; dospělí; ELISA; lidé; Biomarkers; Air Pollutants; Polycyclic Aromatic Hydrocarbons; Enzyme-Linked Immunosorbent Assay; Fetal Blood; Fetus; látky znečišťující vzduch; Adult; plod; biologické markery; ženské pohlaví; fetální krev; Cotinine; těhotenství; Young Adult; Smoking; Maternal-Fetal Exchange; matka - expozice noxám; placenta; kouření; adukty DNA; 7,8-dihydro-7,8-dihydroxybenzo(a)pyren 9,10-oxid; DNA Adducts